Children of promise African-American literature and art for young people - Sullivan, Charles 1933- (New York Harry N. Abrams, Incorporated, 1991)
Poems, prose, photographs, and paintings explore the African-American experience as seen through art and literature by blacks or about black subjects. From slavery and colonial times through the Civil Rights Movement and up to the present, the African-American experiences is vividly evoked through nearly 100 poems, songs, and text excerpts in this beautiful introduction to a fascinating culture designed for young readers.
Includes bibliographical references and index.
Keywords: African Americans -- Literary collections; Children's literature, American; American literature -- African American authors; Art appreciation -- Juvenile literature